Investors' obligations under IIAs: Toward a practical solution - Kraijakr Thiratayakinant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The asymmetric nature of international investment agreements whereby home and host states agree on each other's obligation to protect their respective investors while the investors undertake few, if any, obligations has resulted in something of a legitimacy crisis. This Perspective proposes a practical and readily implementable solution.
Keywords: 330